2020
DOI: 10.1101/2020.12.01.20239574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A two-arm, randomized, controlled, multi-centric, open-label Phase-2 study to evaluate the efficacy and safety of Itolizumab in moderate to severe ARDS patients due to COVID-19

Abstract: An uncontrolled increase in cytokine production may lead to systemic hyperinflammation, vascular hypo-responsiveness, increased endothelial permeability, hypercoagulation, multi-organ dysfunction and eventually death in moderate to severely ill COVID-19 patients. Targeting T-cells, an important driver of the hyperinflammatory response, in the treatment of COVID-19, could potentially reduce mortality and improve survival rates. Itolizumab is an anti-CD6 humanized monoclonal antibody with an immunomodulating act… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Ultimately, nine studies have assessed the treatment/management of the cytokine release syndrome in severe COVID-19 patients and were included in the current systematic review [Figure 1]. [21][22][23][24][25][26][27][28][29] e systematic review revealed two therapeutic contenders that should be utilized in patients suffering from the cytokine release syndrome. A tocilizumab/corticosteroid combination and the second being a therapeutic plasma exchange (TPE).…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, nine studies have assessed the treatment/management of the cytokine release syndrome in severe COVID-19 patients and were included in the current systematic review [Figure 1]. [21][22][23][24][25][26][27][28][29] e systematic review revealed two therapeutic contenders that should be utilized in patients suffering from the cytokine release syndrome. A tocilizumab/corticosteroid combination and the second being a therapeutic plasma exchange (TPE).…”
Section: Resultsmentioning
confidence: 99%
“…Ten trials excluded neutropenic patients, seven of which excluded patients with an absolute neutrophil count (ANC) <500 k/μL and three trials excluded patients with an ANC <1,000 k/μL [19, 25,28,[30][31][32][33]. Seven trials excluded thrombocytopenic patients (platelets <50 k/μL).…”
Section: Exclusion According To Laboratory Criteriamentioning
confidence: 99%
“…Eleven trials excluded patients that treated with any immunosuppression treatment, most of which did not specify the exact medications [12,14,16,18,19,25,26,28,[31][32][33].…”
Section: Exclusion According To the Type Of Immunosuppressive Treatmentmentioning
confidence: 99%
“…Multiple clinical studies observed positive results with Itolizumab in different levels of COVID-19 disease severity [106][107][108]. In severe ARDS, Kumar et al reported greater mortality and recovery benefits with Itolizumab than control [109]. Carbon monoxide (CO) protects against oxidative stress and cell death and suppresses inflammation.…”
Section: Other Therapiesmentioning
confidence: 99%